Transmission Line Model Based on PCB Units and Modified pi Circuits - Pereira, T. G. [UNESP]; Prado, A. J. [UNESP]; Lessa, L. S. [UNESP]; Der Agopian, P. G. [UNESP]; Penchel, R. A. [UNESP]; Ferreira, A. A. [UNESP]; Pissolato Filho, J.; IEEE (Ieee, 2019)
This paper presents the development of a physical model of transmission lines and the analyses of the results obtained from this model. The mentioned model is composed using commercial electrical components such as resistors, inductors and capacitors. These components are used for obtaining a cascade of modified pi circuits. It is used for analyzing the propagation of voltage and current waves in the frequency range from 10 Hz to 1 MHz. It is applied sinusoidal inputs in the mentioned frequency range. The modified pi circuits included RL parallel branches for considering the influence of frequency at the longitudinal parameters of the transmission lines. A digital representation of the cascade of modified pi circuits is introduced in a digital simulator software. The frequency scan is carried out and the transfer function are analyzed basing in this type of software.